2013
DOI: 10.1038/leu.2013.41
|View full text |Cite
|
Sign up to set email alerts
|

Type II EATL (epitheliotropic intestinal T-cell lymphoma): a neoplasm of intra-epithelial T-cells with predominant CD8αα phenotype

Abstract: In this multicentre study, we examined 60 cases of Type II enteropathy-associated T-cell lymphoma (EATL) from the Asia-Pacific region by histological review, immunohistochemistry and molecular techniques. Patients were mostly adult males (median age: 58 years, male:female 2.6:1), presenting with abdominal pain (60%), intestinal perforation (40%) and weight loss (28%). None had a history of coeliac disease and the median survival was only 7 months. Histologically, these tumours could be divided into (i) central… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
174
0
9

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(188 citation statements)
references
References 27 publications
5
174
0
9
Order By: Relevance
“…[1][2][3][4][5][6] In the present study, a high proportion of cases expressed γδ-TCR (10/20, 50%), and six cases were negative for both αβ and γδ-TCR, a finding that differs from the description in the WHO classification, which states that EATL Type II cases express αβ-TCR. Tan et al 7 reported predominant expression of αβ-TCR over γδ-TCR, and Chan et al 8 reported that 78% of Type II EATL cases expressed γδ-TCR. Our results confirm that the expression of γδ-TCR is frequently associated to the EATL Type II in Asia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6] In the present study, a high proportion of cases expressed γδ-TCR (10/20, 50%), and six cases were negative for both αβ and γδ-TCR, a finding that differs from the description in the WHO classification, which states that EATL Type II cases express αβ-TCR. Tan et al 7 reported predominant expression of αβ-TCR over γδ-TCR, and Chan et al 8 reported that 78% of Type II EATL cases expressed γδ-TCR. Our results confirm that the expression of γδ-TCR is frequently associated to the EATL Type II in Asia.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Prevalence of the HLA-DQ2 and DQ8 haplotypes that are frequently found in celiac disease was reported to be low in the Eastern Hemisphere. 7 In Asia, almost all EATL cases are classified as Type II, [6][7][8][9] and because of its low incidence, its pathological mechanism and immunohistological findings remain undefined and poorly understood. However, the association of Type II EATL with autoimmune hemolytic anemia is suggestive of a yet unidentified immunological background.…”
mentioning
confidence: 99%
“…Absence of TCR expression might be a common phenomenon in T-cell lymphoma and was also reported in EATL. 28 Although the mechanism for TCR downregulation remains to be elucidated, lack of TCR in a significant proportion of T-cell type ENKTLs suggests that it might play a role in the pathogenesis of this tumor type. Cytotoxic T(Tc)-cells are key factors in the defense against viral infections.…”
Section: Modern Pathology (2016) 29 430-443mentioning
confidence: 99%
“…In keeping with the normal ratio of IEL subsets, CD8? cases showed predominant CD8aa homodimer expression (77 %), regardless of TCR lineage [61].…”
Section: Peripheral T Cell Lymphoma In Asia 231mentioning
confidence: 99%
“…In a recent Asian collaborative study, patients with EATL were mostly adult males (median age 58 years, male:female ratio 2.6:1), presenting with abdominal pain (60 %), intestinal perforation (40 %), and weight loss (28 %). None had a history of celiac disease, and the median survival was only 7 months [61]. EATL is a neoplasm of intraepithelial T lymphocytes (IEL) [56].…”
Section: Peripheral T Cell Lymphoma In Asia 231mentioning
confidence: 99%